Continuing education of librarians in Croatia : problems and prospects - Horvat, Aleksandra (Array, 2004)
Prior to recent establishment of the Training Centre for Continuing Education of Libarians, training of librarians in Croatia had been organised sporadically by several organisations in the field. For the majority of librarians, however, professional education could have easily ended with diploma, because there has been no legal obligation to attend any form of further education. The first attempt to establish a consistent pattern of continuing educatiob for librarians in the whole country was made when four major organizations in the library field, the National and University Library, Zagreb City Libraries, Croatian Library Association and Department of Information Sciences, Faculty of Philosophy signed an agreement on the establishment of the Training Centre.